1997
DOI: 10.1084/jem.185.7.1153
|View full text |Cite
|
Sign up to set email alerts
|

Early HIV-1 Envelope-specific Cytotoxic T Lymphocyte Responses in Vertically Infected Infants

Abstract: High frequencies of cytotoxic T lymphocyte precursors (CTLp) recognizing HIV-1 laboratory strain gene products have been detected in adults within weeks of primary infection. In contrast, HIV-1–specific CTLp are uncommonly detected in infants younger than 6 mo. To address the hypothesis that the use of target cells expressing laboratory strain env gene products might limit the detection of HIV-1 env-specific CTLp in early infancy, recombinant vaccinia vectors (vv) expressing HIV-1 env genes from early isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…HIV-1 specific CD8 ϩ T cells have been infrequently detected in young infants (37,38), possibly due to HIV-1-induced CD4 ϩ T cell dysfunction (39) or viral sequence variation (40). In a recent study of four neonates with asymptomatic congenital HCMV infection, Marchant et al (41) detected HCMV-specific CD8 ϩ T cell responses to a limited number of MHC class I-restricted viral epitopes commonly detected in adults with latent HCMV infection.…”
mentioning
confidence: 99%
“…HIV-1 specific CD8 ϩ T cells have been infrequently detected in young infants (37,38), possibly due to HIV-1-induced CD4 ϩ T cell dysfunction (39) or viral sequence variation (40). In a recent study of four neonates with asymptomatic congenital HCMV infection, Marchant et al (41) detected HCMV-specific CD8 ϩ T cell responses to a limited number of MHC class I-restricted viral epitopes commonly detected in adults with latent HCMV infection.…”
mentioning
confidence: 99%
“…In children who acquire HIV-1 from their mothers, infection is established in the setting of a developing T-cell repertoire, in the presence of high levels of viral replication, and in the presence of deficient cytotoxic T-cell activity (17)(18)(19)(20)(21)(22), and it might even be expected that the frequency of resting CD4 + T cells with integrated HIV-1 would be higher in infected children. In adults, most of the latent virus in resting CD4 + T cells resides in cells with a memory phenotype (23).…”
mentioning
confidence: 99%
“…Other earlier studies in adult LTNP have shown the ability to neutralize primary isolates and heterologous viruses better than those with disease progression. 4,25 However, Montefiori and colleagues 26 found LTNP were unable to neutralize their replicationcompetent HIV with concurrent autologous serum, which differs from our pediatric subjects on HAART who had detectable ANAB to concurrent RCV. Variation in the ability to mount a NAB response to autologous virus may be a reflection of viral diversity and selective pressure on HIV.…”
Section: Ching Et Almentioning
confidence: 78%